LAW ENFORCEMENT MODEL IN COMMUNITY-BASED WASTE MONITORING AND MANAGEMENT AS A REALIZATION OF GOOD ENVIRONMENTAL GOVERNANCE PRINCIPLES IN WEST SUMATERA, INDONESIA - Puspita, Lona (Universitas Kuningan, 2019)
The increasing number of population and industry will have an impact on the number of waste produced, such as plastic waste, paper waste, and packaging products containing toxic materials. This research aims to create a law enforcement model in community-based waste monitoring and management as a realization of the principles of Good Environmental Governance. The research method used was empirical juridical. The results showed that the law enforcement model adapted in community-based waste monitoring and management to realize good environmental governance in West Sumatra Province is started from the monitoring carried out by the community towards the community members littering or do not do waste sorting in which its results will be reported to the Department of Environment. In addition to being based on regional regulations, the law enforcement model is also carried out in the form of social sanctions in which the persons will be being announced on social media for 30 days or participating in various programs conducted by the Department of Environment for 30 days. Hence, community involvement must start from the management, processing, monitoring, and law enforcement.Â Peningkatan jumlah penduduk dan usaha industri akan memberikan pengaruh terhadap sampah yang akan dihasilkan seperti sampah plastik, kertas, produk kemasan yang mengandung Bahan Beracun Berbahaya. Tujuan penelitian ini adalah bagimana membuat model penegakan hukum dalam pengawasan dan berbasis masyarakat sebagai perwujudan prinsip Good Environmental Governance. Metode penelitian ini bersifat yuridis empiris.Â Hasil penelitian ini model penegakan hukum dalam pengawasan dan pengelolaan sampah berbasis masyarakat demi terwujudnya good environmental governance di Provinsi Sumatera Barat dimulai dari pengawasan yang dilakukan oleh masyarakat terhadap warga yang membuang sampah sembarangan atau yang tidak melakukan pilah sampah, yang hasilnya nanti dilaporkan ke Dinas Lingkungan Hidup kota setempat. Model penegakan hukum yang dilakukan selain berdasarkan Peraturan Daerah setempat juga penegakan hukum dalam bentuk sanksi sosial berupa di umumkan dalam media sosial selama 30 hari atau ikut serta dalam program Dinas Lingkungan Hidup setempat selama 30 hari. Keterlibatan masyarakat harus dimulai dari pengelolaan, pengolahan, pengawasan dan penegakan hukumnya